Two new species of Pachyphlodes from China - Li, Ting; Huang, Kaibing; Xu, Yuyan; Fan, Li (Phytotaxa, 2019)
Pachyphlodes cinnabarina sp. nov. and P. wulushanensis sp. nov. are described and illustrated from Northern China in this paper. Morphologically, P. cinnabarina is distinguished from other species of Pachyphlodes by its orange red ascomata and ascospores ornamented with pin-like spines, while P. wulushanensis by its yellowish-green ascomata and ascospores with spines partly coalescing at apex. Phylogenetic analysis based on ITS and LSU sequences supports the erection of the two new species.